Effect of orthopedic insoles on lower limb motion kinematics and kinetics in adults with flat foot: a systematic review - Chen, Hairong; Sun, Dong; Fang, Yufei; Gao, Shunxiang; Zhang, Qiaolin; Bíró, István; Tafferner-Gulyás, Viktória; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2024)
Flatfoot is characterized by the collapse of the medial longitudinal arch, eversion of the rearfoot and abduction of the loaded forefoot. Orthopedic insoles are the frequently recommended treatment to support the arch of the foot, adjust the structure of the foot, reduce pain, improve stability and new techniques have been applied to the design of orthopedic insoles in recent years. However, the effectiveness of orthopedic insoles in different motions is still debated from the perspective of biomechanics. Therefore, this study aimed to explore the impact of orthopedic insoles on the kinematics and kinetics of lower limb motion, and to verify effectiveness and propose possible future research directions. We conducted a literature search across three databases employing Boolean operations and filtered results based on eligibility criteria. A total of 671 relevant literatures were searched in this review, and 19 literatures meeting the requirements were finally included. The results showed that: (1) orthopedic insoles were effective when patients walk, run and jump from the perspective of biomechanics; (2) orthopedic insoles had different result on the change of ankle sagittal angle, moment and peak pressure in the metatarsal region; (3) Whether the effect of insoles, which uses new techniques such as different 3D printed technologies and adds various accessories, can be further improved remains to be further studied; (4) Follow-up studies can pay more attention to the differences between diverse populations, increase the breadth of running and jumping and other movements research and long-term intervention.